The relationship between unit trust performances towards Kuala Lumpur Composite Index (KLCI) performance in Malaysia: a case study of Amanah Saham Nasional Berhad (ASNB) product / Norhidayu Mohd Norrawi (Faculty of Business and Management, 2008)
This study is about the relationship of unit trust performance towards the KLCI. The Amanah Saham Nasional Berhad (ASNB) has been chosen as the case of this study since it is one of unit trust company in Malaysia. The scope of study started from 1st April 2003 - 1st April 2008 unit trust market return based on Net Asset Value (NAV) and Kuala Lumpur Composite Index (KLCI) market return, using monthly basis. The variables of this study is narrowed and focused on variable pricing product only that are the ASN, ASN 2, ASN 3, ASG Didik, ASG Sihat and ASG Sara fund towards the market performance. The methods use to measure the objectives of the study is simple linear regression. Based on empirical finding the ASN, ASN 2, ASN 3, ASG Didik, ASG Sihat and ASG Sara funds are influenced by the KLCI independent variable. In conclusion, this study rejects the null hypothesis since it shows that all the unit trust performance does have a significant relationship towards KLCI.